2008
DOI: 10.1542/peds.2007-1993
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Medium-Chain Acyl-CoA Dehydrogenase Deficiency Detected by Newborn Screening

Abstract: Newborn screening for medium-chain acyl-CoA dehydrogenase deficiency has detected cases with a wide range of genotypes and biochemical abnormalities. Although most children do well, adverse outcomes have not been entirely avoided. Assessment of potential risk and determination of appropriate treatment remain a challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 23 publications
6
53
0
1
Order By: Relevance
“…It seems that there is no clear relationship between genotype and phenotype (Andresen et al 1997;Lehotay et al 2004;Waddell et al 2006;Hsu et al 2008), but patients homozygous for the common mutation have higher levels of C8 (Andresen et al 2001;Waddell et al 2006;Smith et al 2010), and it is associated with a greater predisposition to suffer decompensation in situations of metabolic stress (Arnold et al 2010). Thus, compound heterozygous for the prevalent c.985A>G mutation and a milder mutation in the other allele may have a risk reduction due to their greater residual enzyme activity (Lehotay et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that there is no clear relationship between genotype and phenotype (Andresen et al 1997;Lehotay et al 2004;Waddell et al 2006;Hsu et al 2008), but patients homozygous for the common mutation have higher levels of C8 (Andresen et al 2001;Waddell et al 2006;Smith et al 2010), and it is associated with a greater predisposition to suffer decompensation in situations of metabolic stress (Arnold et al 2010). Thus, compound heterozygous for the prevalent c.985A>G mutation and a milder mutation in the other allele may have a risk reduction due to their greater residual enzyme activity (Lehotay et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…To date, 81 ACADM mutations have been described in the Human Genome Mutation database http://www.hgmd.cf.ac.uk, but a clear genotypephenotype correlation has not been established, and there is a wide phenotypic variability even within the same family (Yokota et al 1991;Andresen et al 1997;Lehotay et al 2004;Waddell et al 2006;Hsu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This finding can be explained by some residual MCAD function. Hsu also reported a patient with MCADD (c.985A>G and c.127G>A) with marked ketonuria during an intercurrent infection (Hsu et al 2008).…”
Section: Clinical Phenotypementioning
confidence: 95%
“…In these cohorts, the c.985A>G mutation in the ACADM gene accounted for about 90% of disease-causing alleles (Gregersen et al 1991;Yokota et al 1991;Derks et al 2006). In addition to this most common mutation in Europe, in screening cohorts other mutations, especially c.199T>C, are frequently found (Ziadeh et al 1995;Andresen et al 2001;Maier et al 2005;Waddell et al 2006;Hsu et al 2008). There is ongoing discussion, whether patients with this potentially mild mutation would ever show any clinical phenotype (Andresen et al 2001) or might not require treatment at all (Sturm et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several theories have been proposed, including toxic effects of accumulating longchain hydroxy-acylcarnitines, energy deficiency, or deficiency of docosahexaenoic acid (DHA) (Bakermans et al 2011;Fletcher et al 2012;Gillingham et al 2005). Recent research has demonstrated language, motor, and/or developmental delays in patients with FAODs (Brown et al 2014;Hsu et al 2008;Iafolla et al 1994;Joy et al 2009;Waisbren et al 2013), although information on neuropsychological development in LCHADD is very limited. In this report, we present data on neuropsychological outcomes and developments in eight LCHADD patients diagnosed at our centers prior to newborn screening and relate the results to the clinical severity of the disease.…”
Section: Introductionmentioning
confidence: 99%